The Supply of Storage: Stein vs. Snape - Goss, Barry A. (American Economic Review, 1979)
Jerome Stein (1961, 1964) published a porttolio selection model of individual discretionary hedger decision making in a futures trading context, and used this model as a basis for his theory of the simultaneous determination of spot and futures prices. While this model has several limitations (see for example the author and Basil Yamey), it is the purpose of this note to show that it does not have the deficiency attributed to it by Richard H. Snape, who argued that Stein's neglected substitution effect, when accounted for, gives rise to the possibility of an unstable storage market equilibrium. Stein's model determines the proportion of stock to be hedged for a risk-averse individual whose assumed aim is maximization of expected utility. The expected return equations are